Three new species of Macrelmis Motschulsky, 1859 (Coleoptera: Elmidae: Elminae) from the Brazilian Cerrado Biome with updated key for the Macrelmis of Brazil - Barbosa, Felipe Francisco; Fernandes, André Silva; Oliveira, Leandro Gonçalves (Zootaxa, 2013)
Three new species of Macrelmis Motschulsky, 1859 (Macrelmis bispo sp. nov., Macrelmis froehlichi sp. nov., and Macrelmis nessimiani sp. nov.) are herein described and illustrated. The species were collected from several streams in Goiás State, Brazil, a formerly unknown region concerning Elmidae fauna. We also provide an updated key for the Macrelmis species of Brazil.